2022
DOI: 10.1007/s00167-022-07044-w
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tear reaching the superior half portion of the humeral head causes shoulder abduction malfunction

Abstract: Purpose To examine the biomechanical properties governing posterosuperior rotator cuf (RC) tear progression and dynamic shoulder abduction function, in the absence of excess loading. Methods Twelve freshly frozen cadaveric shoulders were evaluated via an established dynamic shoulder abduction stimulator. The shoulder abduction functions were primarily evaluated using subacromial contact pressure (SACP) during an abduction procedure, and subsequent middle deltoid force (MDF) under 5 conditions: (1) intact, (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Of note, the inclusion criteria of the present study were confined to AP-MRCTs, which were reportedly correlated with shoulder dysfunction and a poor prognosis. 17,40,51,52,60 Ernstbrunner et al 17,18 revealed that global extension of RCTs (no remaining rotator cuff attachment above the equatorial line of the humeral head) and the involvement of the inferior subscapularis tendon were strong predictors of chronic pseudoparalysis or pseudoparesis. Compared with anterosuperior and posterosuperior MRCTs, AP-MRCTs demonstrated higher GTE, GFII, and failure rate of arthroscopic rotator cuff repair (18%-56%).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the inclusion criteria of the present study were confined to AP-MRCTs, which were reportedly correlated with shoulder dysfunction and a poor prognosis. 17,40,51,52,60 Ernstbrunner et al 17,18 revealed that global extension of RCTs (no remaining rotator cuff attachment above the equatorial line of the humeral head) and the involvement of the inferior subscapularis tendon were strong predictors of chronic pseudoparalysis or pseudoparesis. Compared with anterosuperior and posterosuperior MRCTs, AP-MRCTs demonstrated higher GTE, GFII, and failure rate of arthroscopic rotator cuff repair (18%-56%).…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutic strategies often involve incorporating anti-inflammatory small molecules into scaffolds, using various techniques such as coatings or blending [ 15 , 16 ]. However, these compounds typically have a short half-life of about one week and are prone to accelerated release kinetics in the dynamic in vivo environment [ [17] , [18] , [19] ]. This rapid release hinders the sustained establishment of an anti-inflammatory niche, thereby impeding tissue regeneration [ [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%